An Integrated Microfluidic‐SERS Platform Enables Sensitive Phenotyping of Serum Extracellular Vesicles in Early Stage Melanomas. (26th July 2021) - Wang, Jing; Kao, Yung‐Ching; Zhou, Quan; Wuethrich, Alain; Stark, Mitchell S.; Schaider, Helmut; Soyer, H. Peter; Lin, Lynlee L.; Trau, Matt
Abstract: Precise detection of early melanomas is essential as the stage of disease guides treatment options. One growing field that may facilitate the advancement of early melanoma detection, is achieved through profiling serum extracellular vesicles (EVs) using sensitive nanotechnology. As a proof of principle, using a detection platform that combines a microfluidic device and surface‐enhanced Raman spectroscopy (SERS), the expression profiles of 4 protein biomarkers in serum EVs (termed as "EV SERS signatures") derived from 20 early stage melanoma patients (including in situ melanoma) and 21 healthy participants are multiplexed. Significantly higher signal intensities of selected protein biomarkers are observed in serum EVs from melanoma patients compared with healthy participants, with mean fold‐changes ranging from 3.7 to 4.2. It is demonstrated that the EV SERS signatures can accurately separate melanoma patients and healthy individuals, with an area under the curve of 0.95. Thus, with further development, this ultra‐sensitive detection platform, combined with the panel of melanoma‐associated biomarkers, has the ability to differentiate early stage melanoma patients from healthy participants. Abstract : A detection platform that integrates a circulating nanomixing‐microchip and a multiplexing surface‐enhanced Raman spectroscopy barcoding system for sensitive phenotypic characterization of serum extracellular vesicles, without extensive sample pre‐enrichment is developed. This platform, combined with the panel of melanoma‐associated biomarkers, has the ability to differentiate early stage melanoma patients from healthy participants.